2017
DOI: 10.3171/2017.8.focus17442
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of perioperative seizure prophylaxis during brain tumor resection: the case for a multicenter randomized clinical trial

Abstract: OBJECTIVEThe majority of neurosurgeons administer antiepileptic drugs (AEDs) prophylactically for supratentorial tumor resection without clear evidence to support this practice. The putative benefit of perioperative seizure prophylaxis must be weighed against the risks of adverse effects and drug interactions in patients without a history of seizures. Consequently, the authors conducted a systematic review of prospective randomized controlled trials (RCTs) that have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The occurrence of seizures before surgery [1, 13, 19, 28, 34], especially if there is a long history of seizures [30] or if the seizures are focal [30] or uncontrolled [3], was positively correlated with seizures postoperatively. However, other studies showed no relationship between preoperative seizures or treatment with anti-epileptic drugs and postoperative seizures [4, 10, 20, 33].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of seizures before surgery [1, 13, 19, 28, 34], especially if there is a long history of seizures [30] or if the seizures are focal [30] or uncontrolled [3], was positively correlated with seizures postoperatively. However, other studies showed no relationship between preoperative seizures or treatment with anti-epileptic drugs and postoperative seizures [4, 10, 20, 33].…”
Section: Discussionmentioning
confidence: 99%
“…31 According to another systematic review of major RCTs, the administration of prophylactic AEDs after brain tumor resection shows no significant reduction in the incidence of seizures compared with that in controls. 32 Similarly, regarding prophylactic antiepileptics in SAH where it is commonly used, propensity score-matched analysis suggests that prophylactic AEDs do not significantly reduce the risk of seizure occurrence. 33 Owing to these recent articles doubting the usefulness of prophylactic antiepileptics in other brain conditions as well, we had undertaken the study on a small scale.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of antiepileptic drugs for intraoperative seizure prevention remains debatable. In a systematic review, antiepileptic drug prophylaxis did not show benefits of seizures prevention in brain tumor resection [ 34 ]. Another systematic review and meta-analysis reported that the efficacy of levetiracetam is superior to that of phenytoin and valproate in terms of seizure prevention [ 35 ].…”
Section: Complications Of Awake Craniotomymentioning
confidence: 99%